(untitled) (Jagannath University Journal of Arts, 2026)
T.S. Eliot is one of the major twentieth-century writers and Nobel laureates in English literature. As a poet of the first rank in both Britain and America, and as a critic with a sharper literary taste than many of his contemporaries, he deeply appreciated the work of the Swedish Academy. Upon receiving the Nobel Prize in 1948, he expressed his belief that it represented the pinnacle of international honors for a writer, not merely as personal recognition but as an acknowledgement of the universal value of poetry. In his acceptance speech for the Nobel Prize, Eliot incorporated his unique Renaissance spirit, literary criticism, philosophical profundity, and spiritual reflections that spoke to the issues of his day. By suggesting that the Nobel Prize is not only a reward but also a responsibility to uphold the values of truth, art, and cross-cultural dialogue, his comments revealed a careful balancing act between humility and responsibility. Eliot’s observations demonstrate how poetry functions as a supra-national language that cuts across boundaries and creates an essential bridge of understanding between nations. As a result, his speech transcends its ceremonial function and turns into a statement of literary philosophy that is still relevant today. Accordingly, this article ventures to critically analyze Eliot’s Nobel banquet speech, setting it against the context of other Nobel speeches of his time, while also revisiting his literary significance as assessed by critics across the world. Jagannath University Journal of Arts, v-15, i-01, 2025:p123-130